Pronunciation Errors of Medical Terminologies Occurred in Students’ Presentitation About Medical Laboratory Procedure - Purianingtyas, Allen Rufaida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Pronunciation becomes the unseparated point in learning active English skills. It is important to be recognized since it is placed as a crucial thing to avoid missed communication. English for Specific Purpose in terms of medical purpose employ the main rules for students in Bachelor Applied Science of Medical Laboratory study program, Poltekkes Kemenkes Semarang. The students’ capability in presenting medical laboratory procedure becomes one of the skill that should be mastered in English subject. Since it is recognized as second language, the students need more attempt to learn especially in active skill aspect. This study elaborated descriptive qualitative method through the analyze of students audio recording about presenting medical laboratory procedure with the topics such as Sputum Sample for TBC Procedure, How to Measure Blood Sugar Level, Taking Feces Sample Procedure, Intermittent Blood Sugar Check Procedure, Medical Procedure about Checking Body Temperature, How to Use Tourniquet in Blood Draw, Peripheral Blood Smear, Hematocrit Examination Procedure, Hand Washing Procedure in Medical Laboratory, Procedure of Capillary Blood Collection, Bacteria Gram Stain Procedure. The data collection were identified in pronunciation errors in medical terminologies especially in the specification of medical laboratory. The vowel substitution more frequently occurred than consonant error. The result showed 62 % of vowel substitution errors and 32% of consonant errors. According to this founding, it can be outlined that there are some factors that influenced these problems such as the intervention of first language, the lack consideration of phonetic importance in English, and the less frequency to spoken English of medical terminology. In the future research, it is hoped that there will be more treatment or activities for improving their skills in speaking English and minimizing the errors of pronouncing medical terminologies since those are concerned as unseparated parts of medical laboratory context. So, it can build good performance in elaborating their skills in presenting medical laboratory procedure in the aspects of accuracy, safety, and professionalism.